Reog Ponorogo Museum with Historical Approach in Sampung Ponorogo Village - Emeralda Diza Pramesti (Faculty Of Arts and Design Sebelas Maret University, 2024)
Arts and culture are an integral part of a nation's identity and should be protected to preserve the values deeply rooted in the lives of Indonesian society. One such art form that deserves preservation is Reog Ponorogo. The uniqueness of Reog Ponorogo necessitates its preservation through an appropriate medium. In an effort to conserve the cultural assets of Ponorogo Regency, the government has established the Reog Ponorogo Monument (MRP) in Sampung Village, Ponorogo. The methodology employed in this study involved data analysis structured using a schematic concept encompassing programming, data analysis, idea development, and design concept development utilizing software such as SketchUp. The outcome of this final project is the design of the interior of the Reog Ponorogo Museum in Sampung Village, Ponorogo Regency, employing a historical approach that will highlight the narrative aspect of the past in museum design.   Keywords: Museum, Reog Ponorogo, History, Narrative